Gene-selective developmental roles of general transcription factors. - Veenstra, G.J.C.; Wolffe, A.P. (Trends in Biochemical Sciences, 2001)
Innumerable transcription factors integrate cellular and intercellular signals to generate a profile of expressed genes that is characteristic of the biochemical and cellular properties of the cell. This profile of expressed genes changes dynamically along with the developmental stage and differentiation state of the cell. The biochemical machinery upon which transcription factors integrate their signals is referred to as the general transcription machinery. However, this machinery is not of universal composition, and variants of the general transcription factors play specific roles in embryonic development, reflecting the constraints and requirements of developmental gene regulation.